2019
DOI: 10.1111/ppl.12893
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic in vitro cultivations: the way to go astray in plant physiology

Abstract: Rate of photosynthesis and related plant carbohydrate status are crucial factors affecting plant vigor. Sugars providing carbon and energy sources serve also as important signaling molecules governing plant growth and development through a complex regulatory network. These facts are often neglected when mixotrophic cultivation of plants in vitro is used, where artificial exogenous sugar supply hinders studies of metabolism as well as sugar‐driven developmental processes. We compared the growth, selected gas‐ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
(70 reference statements)
0
12
2
Order By: Relevance
“…In papaya, using a stationary liquid culture with zeolite supported more rooting and the survival of shoots cultured without sugar and exposed to high ventilation was reported [55]. Within plants cultured in SSM results seem to be more variable: grapevine and kiwi fruit shoots cultured in SSM rooted and acclimatized better with sucrose [56,57], in rapeseed no correlation could be established [45], whereas with thyme, paulownia, potato, tobacco and wasabi more roots were formed when less sugar was added to the culture medium [29,33,45,58]. In strawberry, contradictory reports have been reported, as Ševčíková et al [45] did not observe an increase in the root mass when sugar was not added to the medium, whereas Nguyen et al [29] reported more and longer roots in photoautotrophic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In papaya, using a stationary liquid culture with zeolite supported more rooting and the survival of shoots cultured without sugar and exposed to high ventilation was reported [55]. Within plants cultured in SSM results seem to be more variable: grapevine and kiwi fruit shoots cultured in SSM rooted and acclimatized better with sucrose [56,57], in rapeseed no correlation could be established [45], whereas with thyme, paulownia, potato, tobacco and wasabi more roots were formed when less sugar was added to the culture medium [29,33,45,58]. In strawberry, contradictory reports have been reported, as Ševčíková et al [45] did not observe an increase in the root mass when sugar was not added to the medium, whereas Nguyen et al [29] reported more and longer roots in photoautotrophic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of correlation between photosynthetic pigments and growth has been reported for other plants such as myrtle [43], chestnut [44], apple [28], tobacco, potato, strawberry, and rapeseed [45] and V. condensata [32]. Even if chlorophylls and carotenoids drive photosynthesis by absorbing energy from light, photosynthesis is dependent on other major physiological and biochemical processes including CO 2 stomatal and mesophyll conductance and the biochemistry driven by the Rubisco enzyme system [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad bed and furrow and raised bed land configurations along with residue and hedge leaves mulching under no-till improved soil quality and was the most suitable for higher returns of groundnut-rapeseed system under rainfed condition. Crop rotation: The work of [47] investigated mixotrophic cultivations and found higher instantaneous water use efficiency in photoautotrophic conditions compared to photomixotrophic rapeseed plants. Breeding: The work of [48] investigated two contrasting rapeseed genotypes, Qinyou 8, drought-sensitive, and Q2, drought-tolerant.…”
Section: Other Agronomic Practicesmentioning
confidence: 99%
“…High sucrose concentrations may cause hyperhydricity and other disorders [ 29 ]. It has been claimed that the elimination of sugar from micropropagation nutritive media promotes photosynthetic activity, producing a healthier physiological state and increasing the speed of plantlet adaptation to greenhouse conditions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%